2018
DOI: 10.1038/s41435-017-0006-8
|View full text |Cite|
|
Sign up to set email alerts
|

High resolution HLA analysis reveals independent class I haplotypes and amino-acid motifs protective for multiple sclerosis

Abstract: We investigated association between HLA class I and class II alleles and haplotypes, and KIR loci and their HLA class I ligands, with multiple sclerosis (MS) in 412 European-American MS patients and 419 ethnically-matched controls, using next generation sequencing. The DRB1*15:01~DQB1*06:02 haplotype was highly predisposing (odds ratio (OR) = 3.98; 95% confidence interval (CI) = 3−5.31; p-value (p) = 2.22E−16), as was DRB1*03:01~DQB1*02:01 (OR = 1.63; CI = 1.19–2.24; p = 1.41E−03). Hardy-Weinberg (HW) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 87 publications
3
15
0
Order By: Relevance
“…Of the significantly associated HLA haplotypes and alleles reported by Mack, et al . in Europeans, three were nominally associated with MS in at least one admixed population in this study[18]. In particular, the HLA-DRB1*03 : 01 and HLA-A*02 : 01 alleles in African Americans exhibited similar ORs and direction of effect (Table 5).…”
Section: Discussionmentioning
confidence: 61%
“…Of the significantly associated HLA haplotypes and alleles reported by Mack, et al . in Europeans, three were nominally associated with MS in at least one admixed population in this study[18]. In particular, the HLA-DRB1*03 : 01 and HLA-A*02 : 01 alleles in African Americans exhibited similar ORs and direction of effect (Table 5).…”
Section: Discussionmentioning
confidence: 61%
“… c Associated with Lupus erythematosus (Miyagawa et al, 1997 ). d Associated with central nervous system demyelination and autoimmune disease (Dyment et al, 2005 ; Kaushansky and Ben-Nun, 2014 ; Mack et al, 2019 ) . e Associated with celiac disease (Selleski et al, 2018 ; Farina et al, 2019 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that HLA plays an important role in almost all immune-related diseases, including MS. HLA is divided into HLA-I, -II, and -III regions, of which I and II are the most polymorphic regions in the human genome, which can lead to different combinations of genotypes or haplotypes. Class I contains HLA-expressing A, B, C, and other major sites, and class II mainly includes 3 sub-zones: DP, DQ, and DR [4547]. Since the 1970s, HLA loci have been reported to be associated with MS [48], and the relationship between HLA genes and MS susceptibility has been increasingly studied.…”
Section: Genetics and Smoking-induced Msmentioning
confidence: 99%